DESIGN OF STEAM POWER PLANT PROTOTYPE TO SUPPORT PHYSICS LEARNING IN VOCATIONAL SCHOOL - Sitiadefi, Kuswita
Vocational High School (SMK) is a secondary school with special education to prepare its graduates ready for work. Vocational education is designed to provide student’s experience and skills in certain fields. Project-based learning is a learning method that can provide a good experience for students, both in terms of knowledge and skills. Physics learning in vocational school becomes a basic vocational subject contained in the curriculum structure of the technology and engineering groups, with the proportion 40% for theoretical learning and 60% practical learning. This research aims to produce a product in the form of a prototype of a steam power plant that is used as a teaching media for vocational students so it can improve student’s knowledge and skills. Physics learning in vocational schools currently tends to be given classically, book-oriented and not related to everyday life, even though there is a sufficient physics laboratory. Improper learning approaches cause students to have difficulty understanding concepts, hinder student’s creativity and the assumption that physics lesson are difficult. Physics learning using teaching aid is one of the learning approaches in vocational school that can improve student’s understanding of physics concepts in everyday life and improve student’s skills. This research was conducted through several stages, which are designing product, preparing materials to be used as product components, assembling components and product testing. Based on the experimental results, this PLTU prototype can be used as a physics teaching tool for vocational school students. The resulting boiler engine efficiency is in the range of 23% - 53%. The result of calculating the average boiler heat energy is 641.63 kJ/hour. The maximum power obtained is 240,65 Watt. The resulting voltage is in the range of 29 Volts – 42 Volts.